2012
DOI: 10.1071/mf12072
|View full text |Cite
|
Sign up to set email alerts
|

Development of integrated habitat indices for bigeye tuna, Thunnus obesus, in waters near Palau

Abstract: Abstract.A survey was conducted in waters near Palau in 2005, to improve our understanding of the relationship between environmental variables and the spatial distributions of Thunnus obesus. Catch rates and environmental variables (water temperature, salinity and dissolved oxygen) at six depth strata between 40 and 280 m were collected at 77 sampling stations in the survey. Models were developed to estimate an integrated habitat index (IHI) for T. obesus on the basis of quantile regression. The findings of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…This avoidance is in agreement with other studies such as Sund et al. (), Brill () and Li, Song, Nishida, and Gao ().…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This avoidance is in agreement with other studies such as Sund et al. (), Brill () and Li, Song, Nishida, and Gao ().…”
Section: Discussionsupporting
confidence: 94%
“…For example, both our GAM and Quotient Analysis suggested that bigeye and skipjack avoid waters where the concentrations of oxygen at 150 m depth are less than 1 ml/L. This avoidance is in agreement with other studies such as Sund et al (1981), Brill (1994) and Li, Song, Nishida, and Gao (2012).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, as we tried to kept environmental predictors according to their ecological significance, some correlated variables were retained. For example, we used the vertical shear of ocean current and dissolved oxygen concentration as they were demonstrated the effect of bigeye tuna habitat depths (Brill, 1994; Li et al, 2013), but these variables were correlated with each other and also correlated with the vertical temperature. Though the MaxEnt model could implicitly deal with feature selection based on its own inbuilt method ( e .…”
Section: Discussionmentioning
confidence: 99%